Implementasi Program Kulliyatul Mu’allimin Al-Islamiyah di Pondok Modern Ibadurrahman Tenggarong Seberang Kalimantan Timur - Istiqomah, Ridha; Mahmud, Muchammad Eka; Fauzan, Umar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This research is motivated by the importance of Arabic language skills in understanding Islamic teachings. As a response, the KMI system at Pondok Modern Ibadurrahman implements Arabic-based Islamic Tarikh learning. Tarikh Islam discusses the journey and dynamics of the development of Islam from time to time, including the struggles of the prophets, the spread of Islam, and the triumphs and challenges faced by Muslims. This study not only provides historical insight, but also trains santri in understanding Arabic historical texts. Therefore, this study aims to describe how the implementation of KMI. This research uses a qualitative approach with a case study design. The data sources consist of the Director of KMI, Islamic History teachers in grades 2, 3, and 4, and students in grades 2, 3, and 4 at Pondok Modern Ibadurrahman Tenggarong Seberang. The research instruments used include observation, interviews, and documentation. Data validity is tested through triangulation of sources and techniques. The data analysis technique includes data collection, data condensation, data presentation, and conclusion drawing. The results showed that the implementation of KMI in the subject of Islamic History at Pondok Modern Ibadurrahman Tenggarong Seberang includes learning planning in the form of determining objectives, selecting learning resources, and preparing learning designs according to the KMI syllabus and RPP / I'dat. The implementation of learning in the form of greetings, introductory vocabulary, reading historical texts, and explaining material using Arabic and evaluating learning in the form of daily questions and answers, written questions and mid- and end-of-semester exams. In addition, in the process, this learning also explores the Arabic language skills of students through the aspects of listening, reading, writing and speaking so that students can understand the material in Arabic optimally. Based on these findings, this study suggests further optimizing the strategy of strengthening students' Arabic language skills and utilizing media and other supporting facilities to support the effectiveness of Islamic Tarikh learning.